Depression in adolescent girls : science and prevention - Costanzo, Philip R.; Garber, Judy; Strauman, Timothy J. (Duke series in child development and public policy, 2011)
"Compared to boys, adolescent girls face an increased risk of depression and repeated recurrences throughout adulthood. This unique volume presents a comprehensive multidisciplinary framework for understanding how girls become vulnerable to mood disorders and how that vulnerability might be reduced. The contributors are leading scholars at the cutting edge of theory, research, intervention, and policy. The chapters cover new developments in the science of depression--from genes to biological, psychological, and social processes--and explore how the research is being translated into innovative prevention efforts"-- Provided by publisher